Acute Abdomen Revealing an Unusual Case of Intra-Abdominal Testicular Torsion. (28th December 2019) - Halidou, Maazou; Roua, Amadou; Amadou Magagi, Ibrahim; Adamou, Harissou; Adakal, Ousseini; Rouga, Mohamed; Amadou, Soumana; Sani, Rachid
Abstract : Introduction . Intra-abdominal testicular torsion is a rare event. We report hereby our experience of the management of a spermatic cord twist on intra-abdominal testis discovered during an acute surgical abdomen. Case Presentation . This was a 42-year-old patient admitted to the emergency department for abdominal pain that had been evolving for a week. The physical examination showed tenderness and guarding in the left iliac fossa with an empty ipsilateral hemiscrotum. Complementary examinations led to the discovery of an intra-abdominal left-lateral mass. The laparotomy found a whitish mass with areas of infarction, which was resected. Anatomopathological examination of the operative specimen identified it as a testis with atrophy of germ cells and necrotic areas without evidence of malignancy. Conclusion . Intra-abdominal testicular torsion should be considered in case of patients with an acute surgical abdomen with vacuity of one of the bursae.